In the eye of the beholder: What determines how people sort others into social classes? - Stubager, R; Tilley, J; Evans, G; Robison, J; Harrits, G (Elsevier, 2018)
Contrary to much conventional wisdom, this article shows that class is still used by people to sort others into groups, that this sorting is largely on the basis of income and occupation and that it occurs in conditions of both high and low income inequality. Uniquely, we use both open-ended survey questions and a factorial survey experiment to show that people from high (Britain) and low (Denmark) inequality countries are willing to define classes and they do so mainly in terms of job and income. Even though people in the two countries classify others using somewhat different class labels – with working class labels being used more frequently in Britain than in Denmark – we find a common underlying pattern to the classification. This indicates that class categorization takes place according to a strong underlying mental schema.